The Effect Of Contractor Management On The Quality Of Construction Work In District Of Demak - Nurul Fadhilah (International Conference on Coastal and Delta Areas, 2017)
Several factors influence the performance of the contractor's management on the quality performance of the resultant work. Through management studies on this contractor is intended to provide an overview of what effect is correlated with the quality achievement of construction work in Demak district. The data collection is done by survey method of existing contractor company of middle-qualified (CV) in Demak district. The results of this study indicate that contractor management contributes 82% to the quality performance of construction work in demak district. While some components of contractor management that affect the quality achievement is Planning Variable regression coefficient (X1) of 0, 152 , Organizing Variable regression coefficient (X2) of 0.373, Staffing variable regression coefficient (X3) equal to 0,559, Directing variable regression coefficient (X4) amounted to 0.236, Controlling variable regression coefficient (X5) amounted to 0.133 Keywords: Management, Contractors, Quality Work